School Racial Segregation and Late-Life Cognition - Zhuoer Lin; Yi Wang; Thomas M. Gill; Xi Chen (Institute of Labor Economics (IZA), 2024)
Disparities in cognition persist between non-Hispanic Black (hereafter, Black) and non-Hispanic White (hereafter, White) older adults, and are possibly influenced by early educational differences stemming from structural racism. However, the relationship between school racial segregation and later-life cognition remains underexplored. We examined a nationally sample of older Americans from the Health and Retirement Study. Utilizing childhood residence data and cognitive assessment data (1995-2018) for Black and White participants aged 65 and older, Black-White dissimilarity index for public elementary schools measuring school segregation, multilevel analyses revealed a significant negative association between school segregation and later-life cognitive outcomes among Black participants, but not among White participants. Potential mediators across the life course, including educational attainment, explained 58-73% of the association, yet the associations remained large and significant among Black participants for all outcomes. Given the rising trend of school segregation in the US, educational policies aimed at reducing segregation are crucial to address health inequities. Clinicians can leverage patients' early-life educational circumstances to promote screening, prevention, and management of cognitive disorders.
Keywords: I14; I24; I10; J14; J15; H75; 330; early-life circumstances; school segregation; quality of education; racial disparity; cognition; dementia; health equity